Managing legitimacy through corporate community involvement: The effects of subsidiary ownership and host country experience in China - Baik, Youjin (Springer Nature, 2020)
This article examines the legitimacy rationale behind the corporate community involvement of foreign subsidiaries in China from an institutional perspective. Based on the assumption that the level of community involvement reflects a firm’sdesiretoseek legitimacy in the host country, we suggest two research questions: 1) How do factors determining the need for legitimacy affect foreign subsidiaries’ community involvement? and 2) How can these relationships be moderated by perceived trust in local business relationships? We hypothesize that a foreign parent’s ownership share has a positive effect on its subsidiaries’ local community involvement, while sufficient host country experience leads to less community involvement. We also propose that the level of perceived trust toward local business partners moderates these impacts of parent firm ownership and host country experience on local community involvement. These hypotheses are generally supported by our analysis of 223 Korean subsidiaries in China.